2021
DOI: 10.1158/1940-6207.capr-21-0091
|View full text |Cite
|
Sign up to set email alerts
|

The Chasm We Must Cross in Japan for Re-promotion of the HPV Vaccine

Abstract: In Japan, the human papillomavirus (HPV) vaccination rate has decreased from around 70% to less than 1% due to repeated media reports of diverse symptoms after HPV vaccination, and to suspension of the governmental recommendation. The challenges for re-promotion of the vaccine will be discussed from a marketing perspective. The adopter categories by which a new product penetrates the market can be divided into five groups, including Innovators, Early adopters, Early majority, Late majority, and Laggards. The 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Consequently, the HPV vaccine continues to have a strong negative image in Japan. 44,45 In Japan, the incidence of cervical cancer is rapidly increasing among young female individuals, and its prevention using adequate HPV vaccination is crucial. 46 We proposed various vaccination coverage dissemination strategies to restore HPV vaccination coverage as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the HPV vaccine continues to have a strong negative image in Japan. 44,45 In Japan, the incidence of cervical cancer is rapidly increasing among young female individuals, and its prevention using adequate HPV vaccination is crucial. 46 We proposed various vaccination coverage dissemination strategies to restore HPV vaccination coverage as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…In October of 2020, the MHLW revised its public information leaflet for the HPV vaccine, and they advised all local governments of the proven effectiveness of providing an individual notification to girls in the targeted age-range [ 24 ]. In Japan, we have now shown that positive peer education is going to be essential to overcome the cascade of negative social pressures that have accumulated against HPV vaccination [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…From this, they recognized that successful interventions would need to start with recruiting early adopters, instead of persons later in the diffusion cycle (Rosen & Goodson, 2014). In Japan, DOI has been used to explore phases of public health education campaigns to move between each stage of the diffusion cycle (Ueda, Katayama, Yagi, & Kimura, 2021). DOI has also been suggested as a model for understanding and exploring healthcare policies generally (Dearing & Cox, 2018), and more recently has been used to evaluate intention to receive COVID-19 vaccination in China (Mo et al, 2021).…”
Section: Diffusion Of Innovationmentioning
confidence: 99%